Green Revolution in Ready Made Garments in Bangladesh: An Analytical Study - Md. Abdul Awal; Md. Elius Hossan; Md. Aliullah; Md. Shishir Saidy (International Journal of Engineering and Management Research, 2021)
Bangladesh, a small south Asian country, holds the second position in the world of exporting readymade garments (RMG). Here locate the highest number of green RMG factories in the world. Green industrialization is the positive symbol of sustainable development. This paper represents an impressive illustration of the scenario of RMG industries in Bangladesh especially the growth, contribution to export and the success of LEED (Leadership in Energy and Environmental Design) recognized Platinum, Gold and Silver factories. This paper also represents the success of green revolution in RMG industries in Bangladesh and recommends some suggestions to convert the traditional industries to green industries where the industries are not only for making profit but also committed to provide good working environment for employee, eco-friendly and ethical business practice.